POLA SISTEM PENGUPAHAN BAWON BURUH TANI PADA MASA MUSIM PANEN: TINJAUAN ANALISIS KUALITATIF - Novitasari Novitasari (University of Jember, 2021)
This study aims to analyze the pattern of the bawon wage system for farm laborers during the rice harvest season in Selopuro Village. The research location is in Selopuro Village, Selopuro District, Blitar Regency. This study uses a qualitative method. The analytical method used is descriptive method. The results showed that in the wage system pattern of agricultural laborers in the rice harvest season in the form of bawon which was accompanied by a wage sharing payment in the form of giving rice or unhulled rice. In the implementation, the rice harvest is carried out in groups and the performance of farm works is carried out well. The reason for using the bawon wage system in Selopuro Village, Blitar Regency is that the community wants to preserve the tradition, maintain the value of mutual cooperation so that it remains today, and in the bawon wage system it is able to provide benefits for farms workers and landowners so that the bawon wage system remains there is. Meanwhile, the participation of farm workers in the Bawon wage system is carried out in a way that is full of enthusiasm and hard work in harvesting rice. The Bawon wage system pattern is able to have positive and negative impacts because it has advantages and disadvantages, especially for rice field owners and agricultural laborers.